The Glutamate System as a Crucial Regulator of CNS Toxicity and Survival of HIV Reservoirs - Gorska, Anna Maria; Eugenin, Eliseo A. (Frontiers in Cellular and Infection Microbiology, 2020)
Glutamate (Glu) is the most abundant excitatory neurotransmitter in the central nervous system (CNS). HIV-1 and viral proteins compromise glutamate synaptic transmission resulting in poor cell-to-cell signaling and bystander toxicity. Furthermore, we identified that myeloid HIV-1-brain reservoirs survive in Glu and glutamine (Gln) as a major source of energy. Thus, we found a link between synaptic compromise, metabolomics of viral reservoirs, and viral persistence. In the current manuscript we will discuss all these interactions and the potential to achieve eradication and cure using this unique metabolic profile.